Haemolysis in haemodialysis. Issue 11 (17th October 2017) - Tharmaraj, Dhakshayini; Kerr, Peter G
Summary at a Glance: This is a review article on haemolysis in haemodialysis patients, highlighting the causes, investigation and management of such clinical situations. ABSTRACT: Haemolysis in haemodialysis, although rare in current times, is associated with significant mortality and morbidity. As such prompt recognition, treatment, analysis of root cause and correction of underlying causative factors is crucial. Dialysate, extracorporeal circuit and patient related factors all contribute to haemolysis risk. Haemolysis can manifest with non‐specific signs and symptoms including but not restricted to hypertension, nausea, pain (abdominal, chest, back) and dyspnoea. It may present acutely during the dialysis session or may take a protracted course. Potential life threating consequences include; hyperkalaemia induced cardiac arrhythmias, profound anaemia and associated acute coronary events and respiratory distress, and severe necrotizing pancreatitis. Chronic haemolysis results in impaired endothelial function thus contributing to the long‐term cardiovascular risk profile in haemodialysis patients. Stringent national and international standards, technological advancements in membrane and dialysis equipment design, dialyser purification methods and water treatment systems have greatly reduced the incidence of haemolysis. Despite these improvements recognition of haemolysis risk and ongoing clinical vigilance is important.